SCRIPTURE, STORY, AND SPIRITUALITY: INTERPRETING HINDU TEXTS THROUGH LITERARY LENSES - I Wayan Artayasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study explores the intersection of scripture, narrative, and spirituality in Hindu literary traditions through a hermeneutic literary lens. By examining the Vedas, Itihāsa, and Purāṇas, it argues that Hindu scriptures are not merely doctrinal texts but narrative theologies that use story as a medium of revelation. Through poetic symbolism, metaphor, and mythic imagination, Hindu texts communicate ethical insight and spiritual truth accessible to both scholars and devotees. Using qualitative hermeneutic analysis, the study interprets how narrative structures embody dharma, how myth functions as a vehicle for theological reflection, and how the act of reading itself becomes a form of sādhanā (spiritual practice). The findings reveal that Hindu literature integrates rational exposition with imaginative revelation, transforming scripture into a living dialogue between divinity, language, and human consciousness.